Principles of Accounting - Tran, Thi Thuy Anh (Khoa Quốc tế, ĐHQGHN, 2020)
This course aims to introduce the basic principles of accounting concepts and application in a business environment. The course focuses on concepts such as theory of debits and credits, the accounting cycle, receivables and payables, accruals and deferrals, measurement and valuation of assets and liabilities, and the preparation and analysis of basic financial statements.